El cos, construccions artificials - Negre Busó, Marta (2019)
This article analyses works by Aziz + Cucher, Inez van Lamsweerde and Keith Cottingham, who work on the topic of the human body by means of digital photography in order to show the main problems of the technological world. Through simulation they show portraits and nudes that play with the ambiguity between what is natural and what is artificial